Character assassination throughout the ages - Icks, Martijn; Shiraev, Eric.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Using a variety of cases from history and today's life, the book examines character attackers targeting the private lives, behavior, values, and identity of their victims. Numerous historical examples show that character assassination has always been a very effective weapon to win political battles or settle personal scores.
Keywords: Science; Science; Science, general